ABAQUS Implementation to Analyze the Stress Intensity Factor for Laminated Composite Plate. Issue 1 (December 2020) - Lal, Achchhe; Vaghela, M. B.
Abstract: The objective of this work is Abaqus implementation to analyze the effect of fibre orientation angle on stress intensity factor for Single Edge Notched (SEN) 3D laminate composite plate under tensile loading by various cases. The Abaqus software is used to analyze the various problems through the extended finite element method (XFEM). The effects of various fibre orientation angles on Sress Intensity Factor (SIF), Von Misses stress and displacement are also investigated. The presented work would be useful for enhancing the use of Abaqus software to analyze the composite structure with crack and other discontinuities under various conditions.